An Informed Pedagogy of Community, Care, and Respect for Diversity: Evidence from a Qualitative Evaluation of Early Years Services in the West of Ireland. Issue 3 (3rd July 2017) - Garrity, Sheila; Moran, Lisa; McGregor, Caroline; Devaney, Carmel
ABSTRACT: This article draws on qualitative evidence from an evaluation of the "Greater Tomorrow" Crèche and Ballyhaunis Community Preschool in Ballyhaunis, Co Mayo, Ireland in 2016. The article focuses on the approach to practice and the underlying ethos of these two services, reflecting a clearly articulated respect for diversity and the privileging of relationships with families by the practitioners and management team. We argue for the significance of early years services in offsetting risk factors associated with adverse childhood experiences and environments, reflecting international research evidence for the potential benefits of high-quality early childhood education and care. The practice orientation within the settings operationalises the national quality and curriculum frameworks of Aistear and Síolta in foregrounding the concepts of identity and belonging, well-being, and partnership with families in daily practice. The services under study were established during a period of rapid social and cultural change in Ireland; heightened economic activity beginning in the mid-1990s was a catalyst for increasing female employment and inward migration. This article argues that in such a context, these services responded to the needs of the uniquely diverse community they serve, contributed to children's early learning and development, and provided material and emotional supports to children and parents.